Proceso atención de enfermería en embarazada de 37,4 semanas de gestación más sífilis. - Palma Torres, Cristhian Andrés (2021)
Syphilis is a sexually transmitted disease caused by the Treponema Palladium bacteria. The present clinical case is about a pregnant adolescent, who went to the obstetric emergency area, the patient presented contractile pain upon admission, the obstetrician on duty assesses her and indicates that she went into labor, in which the patient reported that had a history of untreated syphilis, laboratory test confirms positive for syphilis. The objective of this study was to apply the nursing care process to a 17-year-old pregnant woman with a diagnosis of 37.4-week pregnancy plus syphilis. Through an assessment with the Functional Patterns according to Marjory Gordon, the affected patterns were detected and analyzed, which were used as a starting point for the elaboration and application of nursing interventions, aimed at satisfying the needs of the patient, managing to improve the conditions health of it.